2002
DOI: 10.1111/1468-5957.00448
|View full text |Cite
|
Sign up to set email alerts
|

Board Composition in New Zealand: An Agency Perspective

Abstract: This paper looks at board composition determinants in New Zealand. We document that the proportion of outside board members is inversely related to insider equity ownership supporting the notion that these variables are substitute mechanisms in controlling agency problems. We also find that board composition is directly related to debt, ownership concentration, and profitability and inversely related to growth and firm size. There is evidence that firms with influential CEOs have lower outside board representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
75
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 42 publications
10
75
2
1
Order By: Relevance
“…At the (Bd.Index) that measures the effectiveness of the board, a negative and statistically significant relationship was observed between this variable and managerial ownership for two cases which confirms that these two mechanisms are substitutable to ensure an alignment of interests between the manager and shareholders (Prevost et al 2002).…”
Section: Endogeneity Problemsupporting
confidence: 52%
“…At the (Bd.Index) that measures the effectiveness of the board, a negative and statistically significant relationship was observed between this variable and managerial ownership for two cases which confirms that these two mechanisms are substitutable to ensure an alignment of interests between the manager and shareholders (Prevost et al 2002).…”
Section: Endogeneity Problemsupporting
confidence: 52%
“…However, Bhagat and Black (2002) find a negative association between the proportion of outside directors and firm value. On the other hand, Prevost et al (2002) and Connelly and Limpaphayom (2004) do not find a statistically significant relationship.…”
Section: Outside Directorsmentioning
confidence: 85%
“…We further noted that while there are a few studies that have investigated the determinants of internal audit, the effects of ownership structure on the use of internal audit have remained quite unexplored. This was considered a significant research gap, considering that prior research has indicated that ownership structure tends to shape the behavior of firms (Bozec & Bozec, 2007;Dogan & Smyth, 2002;La Porta et al, 2000;Prevost et al, 2002;Rediker & Seth, 1995). The ownership determinants examined in this study include foreign ownership, state ownership, dispersion of ownership, and the influence of a single powerful shareholder.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The literature has demonstrated that it is associated with factors such as corporate governance (Bozec & Bozec, 2007;Desender et al, 2013;Shleifer & Vishny, 1997), firm performance (Burkart et al, 1997;Shleifer & Vishny, 1986;Thomsen & Pedersen, 2000), board composition (Rediker & Seth, 1995;Prevost et al, 2002;Bozec & Bozec, 2007), board remuneration (Dogan & Smyth, 2002), firm value (Jensen & Meckling, 1976;Selarka, 2005;Shleifer & Vishny, 1986;Slovin & Sushka, 1993;Perrini, Rossi, & Rovetta, 2008), dividend policies (La Porta, Lopez-De-Silanes, Shleifer, & Vishny, 2000), investor protection (La Porta, Lopez-De-Silanes, Shleifer, & Vishny, 1998), and mergers and acquisitions activities (Coates, 2010), among others.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%